Implementation of SHARP: A Summer Home Reading Program for Early Learners - Arca, Quenny; Ortizo, Gaudy (Journal of Interdisciplinary Perspectives, 2025)
The study assessed the implementation of the Summer Home Assistance in Reading by Parents (SHARP) Program for Early Childhood Education. It developed an enhanced implementation and contextualization of the SHARP Program based on the study's findings. A validated survey questionnaire with five (5) indicators each was used and was answered by 30 participants chosen following the inclusion criteria from the schools located in Cluster II, Lake Sebu District. The collected data were analyzed and interpreted using mean percentage and Pearson-coefficient correlation coefficient to determine the extent of implementation, as well as the contextualization, and the significant relationship between SHARP Program implementation and contextualization. The results showed that the implementation of the SHARP Program was extensive. Meanwhile, the extent of contextualization of the SHARP Program revealed a high extent of contextualization; however, the content of reading materials demonstrated a moderate extent of SHARP Program contextualization. Moreover, there is a significant relationship between the implementation and contextualization of the SHARP Program. Essential recommendations were made regarding early childhood education. This implies that the program requires further enhancement to become more effective. This means that the program needs further enhancement to become more effective. This allows the researcher to create an enhanced matrix that can be adapted to further help with the implementation of the program.